Heritage Preservation as Strategy for Recomposing Conflict Territories - Jose Manuel Pages Madrigal (Journal of Contemporary Urban Affairs, 2021)
Heritage admits diverse readings depending on different territorial spaces, contexts, and knowledge fields. The relation between Heritage and the social contexts is one of these knowledge areas. But Heritage accepts a dual perception as a cultural reflection. It may be considered either as the origins of the conflicts or the engine for recomposing disrupted territories. The paper proposes a reflection on the topics related to conflict territories and the roles currently played by Cultural Heritage. The recomposition of conflict territories is based on a continuous intercultural approach with important contributions from human rights, genders equality, intercultural dialogue perspectives and the fact of taking heritage as a territorial stabilization factor. The paper presents specific practical cases in the Eastern Mediterranean region where actions on Heritage religious elements collide with the national sovereign of the respective current countries. A comparative study among these different actions proves that the initial clashes can be progressively transformed into strategies able to become the future guideline for the resolution of heritage regional conflicts. These conflicts reflect two discourses: political (with strong links between national identity and religion) and scientific (with a clash between static concept and dynamic vision) where objects interact with the visitors.